2022
DOI: 10.1111/1467-8462.12497
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Implications of Changes in Corporate Tax Rates: A Review

Abstract: Many countries have initiated structural reforms in corporate income tax (CIT) to attract investment and promote growth. There has been a continuous decline in CIT rates worldwide. It is expected that cuts in CIT rates may increase after‐tax profits and encourage investment. A change in the CIT rate may also be shifted backward (by changing salaries and wages) and/or forward (by changing product prices). These are theoretical possibilities and may not have support from empirical evidence. In this paper we revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Finocchiaro andRizzo (2014) andPapanikolaou (2021), through econometrics, showed that when people are in a condition of inequity, they are significantly more likely to evade taxes than in conditions of equity. Murphy, Chistensen, and Kimmis (2005); Bachas, Gadenne, and Jensen (2020)and Mukherjee and Badola (2023) consider that tax justice is a primary factor for the state to obtain income from taxes. Pérez (2014) estimates that through an increase in horizontal equity, it is possible to improve collection efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finocchiaro andRizzo (2014) andPapanikolaou (2021), through econometrics, showed that when people are in a condition of inequity, they are significantly more likely to evade taxes than in conditions of equity. Murphy, Chistensen, and Kimmis (2005); Bachas, Gadenne, and Jensen (2020)and Mukherjee and Badola (2023) consider that tax justice is a primary factor for the state to obtain income from taxes. Pérez (2014) estimates that through an increase in horizontal equity, it is possible to improve collection efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%